Electrochemical impedance spectroscopy as a tool in the plate making process optimization - Cigula, Tomislav (Acta chimica slovenica, 2012)
The structure of the porous aluminium-oxide layer, which builds non-image areas, has the most significant influence on the quality of final graphical product. This paper presents the results of the application of EIS in the characterisation and detection of changes on the aluminium-oxide layer caused by chemical processing in highly alkaline solution. The Al2O3 layer was characterised using SEM, fractal dimension and surface free energy calculationand EIS analysis. The results of the investigation showed that chemical processing has a significant influence on the structure of aluminiumoxide which could lead to a decrease in the quality of the printing plate. EIS enables the detection of changes on the aluminium- oxide layer. Thetwo equivalent circuits are proposed. Based on modelling with the obtained EIS spectra, precise evaluation of developing time in which complete removal of the photoactive layer is achieved. This makes EIS a powerful tool in optimizing chemical processing of lithographic printing plates.
Keywords: aluminijev oksid; elektronska mikroskopija; impedančna spektroskopija; tiskarske plošče